ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEDALAMAN JANGKAUAN (DEPTH OF OUTREACH) LEMBAGA KEUANGAN MIKRO (LKM) UED-SP DI KECAMATAN RAMBAH KABUPATEN ROKAN HULU - Siswanto Siswanto; Eri Sayamar; Ahmad Rifai (Jurnal Ilmiah Pertanian, 2017)
This study analyses the factors affecting the depth of outreach of Microfinance Institutions (MFIs) of UED-SP at Rambah Sub-district Rokan Hulu District. Factors thought to influence the depth of outreach is age of UED-SP, ROA, percent of trading sector clients, percent of agriculture sector clients and number of woman clients. The sampling method is done using by purposive sampling. This study obtained a sample of twelve UED-SPs in the village at Rambah District from in the period of 2012-2015. The data used is secondary data form pooled data. Data were obtained based on the financial reports of each of the samples. This study uses quantitative approach with analysis technique used is multiple linear regression analysis with fixed effect method of pooled data that were previously tested with the classical assumption test. Hypothesis testing using t-statistic and the F-statistic with 95% confidence level. Based on the classic assumption test found no variables that deviate. This shows that the available data has been qualified using the linear regression equation model. The results of this study show that depth of outreach are statistically significant infiuenced by age of UED-SP. However, it’s negatively affect on depth of outhreach. Whereas ROA, number of woman borrower, percent of agriculture sector clients and percent of trading sector clients has no affect on depth of outhreach. Predictive ability of these five variables on the depth of outhreach is 77,66 percent, while the 22,34 percent influenced by other factors not included in the research model.